Symbolic violence in undergraduate LGBT students’ experiences - Moretti-Pires, Rodrigo Otávio; Vieira, Marcelo; Finkler, Mirelle (Saúde e Sociedade, 2023)
Since childhood, symbolic violence has been a process experienced by LGBT people facing the sanctions of hegemonic heteronormativity. University is a space of possibility and change for many people, with a particular expectation: of greater openness to moral plurality and, thus, diversity. This article investigates experiences of symbolic violence, and the contours of the habitus lived by LGBT university students, by using unstructured interviews with 16 students, analyzed from the theoretical framework of Bourdieu. Symbolic violence was present in all their lives, showing itself in different environments and institutions, including the university academic life, but mostly on their family and school life. Facing impositions of the heterosexual habitus, individuals develop resources, with the acquisition of social capital, such as LGBT militancy, standing out. However, the university needs to concretize specific actions to face violence and respect diversity, considering its role as an institution socially responsible for the education of citizens on top of professionals. This is a challenge already present in the definition of the ethical-political university agenda, that becomes even more complex in times of struggle for the very maintenance of the democratic system in the Brazilian State.